Neurointerface with oscillator motifs for inhibitory effect over antagonist muscles - Mikhailova, Yulia; Pozdeeva, Anna; Suleimanova, Alina; Leukhin, Alexey; Toschev, Alexander; Lukmanov, Timur; Fatyhova, Elsa; Magid, Evgeni; Lavrov, Igor; Talanov, Max (Frontiers in Neuroscience, 2023)
The inhibitory management effect is usually underestimated in artificial control systems, using biological analogy. According to our hypothesis, the muscle hypertonus could be effectively compensated via stimulation by bio plausible patterns. We proposed the approach for the compensatory stimulation device as implementation of previously presented architecture of neurointerface, where (1) neuroport is implemented as DAC and stimulator, (2) neuroterminal – as neurosimulation of a set of oscillator motifs on one-board computer. In the set of experiments with 5 volunteers we measured the efficacy of motor neuron inhibition via antagonist muscle or nerve stimulation registering muscle force with and without antagonist stimulation. For the agonist activation, we used both voluntary activity and electrical stimulation. In the case of stimulation of both agonist and antagonist muscles and nerves, we experimented with delays between muscles stimulation in the range 0–20 ms. We registered the subjective discomfort rate. We didn’t identify a significant difference between antagonist muscle and nerve stimulation in both voluntary and stimulation of agonist activity cases. We determined the most effective delay between stimulation of agonist and antagonist muscle/nerve as 10–20 ms.